دراسة آلية تآكل مسخنات هواء الاحتراق في مراجل توليد البخار في مصفاة بانياس - عمّار, سندس غسّان (Latakia University Journal -Engineering Sciences Series, 2014)
يقدم البحث دراسة تحليلية شاملة لتحديد مشكلة التآكل التي تتعرض لها مسخنات هواء الاحتراق في مراجل توليد البخار في مصفاة بانياس ، وذلك من خلال إجراء دراسة تفصيلية لواقع عمل هذه المسخنات تتضمن دراسة : (نوع الوقود المستهلك في الحراقات ، درجات حرارة غازات العادم الفعلية ، وإجراء تحليل كيميائي لنواتج هذه الغازات) . كما يتضمن البحث إجراء تجارب عملية لفحص التآكل في مسخنات الهواء من خلال تحضير كوبونات معدنية من نفس نوع معدن المسخنات تزرع مدة محددة في مجرى غازات العادم بالقرب من المسخن الأول الذي يدخل إليه الهواء أولاًّ ، وإعداد تقارير لذلك ، مع إجراء تحاليل كيميائية لترسبات سطح الكوبون المدروس . تخلص الدراسة إلى أن المسخن الأول يتعرض لتآكل كبير حيث تنخفض درجة حرارة سطحه إلى ما دون نقطة الندى ، ولذلك تم اقتراح تصميم جديد لهذا المسخن من خلال تحديد سطوح التبادل الحراري بين هواء الاحتراق وغازات العادم بحيث تبقى درجة الحرارة أعلى من نقطة الندى مما يقلل من تآكل هذا المسخن بشكل كبير . The search comprehensive analytical study to determine the problem erosion experienced by air heaters combustion in boilers to generate steam in Banias refinery, through a detailed study of the reality of the work of these heaters include: study (type of spent fuel in the burner, temperature exhaust gases actual, and analysis chemical products of these gases). It also includes research testing process to check corrosion in air heaters by preparing coupons metal of the same type metal heaters are grown for specific stream of exhaust gases near the heated first enters the air first, and prepare reports for it, with a chemical analysis of the sediment surface studied Coupon. The study concludes that the heated first exposed to significant erosion where low surface temperature below the dew point, therefore been proposed a new design for this heated by determining surface heat exchange between combustion air and exhaust gases so that the temperature stays above the dew point, which reduces erosion thisheated significantly.